The Relationship between Fluorescein Angiography Leakage after Infliximab Therapy and Relapse of Ocular Inflammatory Attacks in Ocular Behçet's Disease Patients. (16th November 2020) - Shirahama, Shintaro; Kaburaki, Toshikatsu; Matsuda, Junko; Tanaka, Rie; Nakahara, Hisae; Komae, Keiko; Kawashima, Hidetoshi; Aihara, Makoto
ABSTRACT: Purpose : To clarify the relationship between fluorescein angiography (FA) leakage after infliximab therapy and ocular attack relapse in patients with ocular Behçet's disease (BD). Methods : Patients with ocular BD were divided into two groups based on the presence (Group 1) or absence (Group 2) of ocular attacks after IFX therapy. FA leakage was evaluated by FA score in each of the optic discs, macula, large retinal vessels, and capillary vessels. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the relationship between FA score after IFX therapy and ocular attack relapse. Results : The areas under the curves obtained from the ROC curve of optic disc score and capillary vessels score after IFX therapy were 0.867 (95% confidence interval [CI]: 0.788–0.946) and 0.788 (95% CI: 0.649–0.927), respectively. Conclusions : FA leakage in the optic disc and capillary vessels after IFX therapy was strongly related to ocular attack relapse.